The effect of macroprudential policies on credit developments in Europe 1995-2017 - Katarzyna Budnik (European Central Bank (ECB), 2020)
The paper inspects the credit impact of policy instruments that are commonly applied to contain systemic risk. It employs detailed information on the use of capital-based, borrowerbased and liquidity-based instruments in 28 European Union countries in 1995-2017 and a macroeconomic panel setup. The paper finds a significant impact of capital buffers, profit distribution restrictions, specific and general loan-loss provisioning regulations, sectoral risk weights and exposure limits, borrower-based measures, caps on long-term maturity and exchange rate mismatch, and asset-based capital requirements on credit to the non-financial private sector. Furthermore, the business cycle and monetary policy influence the effectiveness of most of the macroprudential instruments. Therein, capital buffers and sectoral risk weights act countercyclically irrespectively of the prevailing monetary policy stance, while a far richer set of policy instruments can act countercyclically in combination with the appropriate monetary policy stance.
Keywords: E51; E52; G21; 330; macroprudential policy; monetary policy; capital requirements; borrower-based instruments; liquidity requirements